Studies in Health Technology and Informatics Volume 23 - Health, Information Society And Developing Countries - Sos‘a-Iudicissa, Marcelo C. (IOS Press, 2014)
The publication of this book was financed by the European Commission, Directorate General XIII, Telecommunications, Information Market and Exploitation of Results. The EpiAim study carried out during 1994, including the two international workshops that took place within its realisation and the previous collaboration in the context of the WHOMANTEAU project (1992-93), were carried-out with the financial support of the European Commission DG XIII and converging efforts of other EC services and from organisations listed below. To them, and to their representatives, many thanks. The editors express their thanks for the important assistance provided by Ms. Christine Asmussen, Consultant to the European Public Health Alliance (EPHA), and former Scholar of the European Parliament Technology Evaluation office (STOA), in the preparation and editing of this book.